Salivary lactate dehydrogenase (LDH) as a tool for early diagnosis of oral cancer in individuals with Fanconi anemia. (October 2018) - Mafessoni, Talita Piassa; Mazur, Carolina Eurich; Amenábar, José Miguel
Abstract: Currently one of the greater challenges is the diagnosis and treatment of cancer. Many studies address the genetic and metabolic aspects to support in early diagnosis and increase the survival of individuals at high risk. Individuals with Fanconi anemia can be included in this high risk group because they have a predisposition to develop head and neck cancer. The use of salivary enzymes as biomarkers to detect the changes in oral tissue at the initial phase seems viable, because saliva is easy to obtain, it moisture oral mucosa and cells metabolic compounds can be found on it. Due to the metabolic characteristics of the cancer cell, an increase in Lactate Dehydrogenase (LDH) may indicate a carcinogenesis process. The hypothesis of this study is to use of salivary LDH as a tool in the early diagnosis of oral cancer on a high risk group such as Fanconi anemia's patients.